Beyond Social Skills: Supporting Peer Relationships and Friendships for School-Aged Children with Autism Spectrum Disorder - Rodda, Amy; Estes, Annette (Seminars in Speech and Language, 2018)
Social impairments are the sine qua non of autism spectrum disorder (ASD). However, children with ASD are capable of forming reciprocal friendships and many people with ASD have a strong desire for friends. Developing and maintaining friendships is associated with many important outcomes, including improved quality of life, mental health, and academic achievement. Children with ASD often attend groups to improve social skills, but strategies for building and maintaining friendships are not consistently addressed or measured following intervention. In this article, our objective is to build an understanding of peer relationships and friendships in school-aged children with ASD and how to best support them. In this article, we describe characteristics of peer relationships and friendships for children with ASD. We discuss current research findings on intervention to improve social skills, peer relationships, and friendships in school-aged children with ASD. Finally, we give suggestions for clinical practice and future research.
Keywords: Autism; peer; relationship; social skills; friendship